Analisis Butir Soal Ujian Sekolah Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VI SDN Kota Bengkulu Tahun Pelajaran 2019/2020 - yusnia yusnia; Badeni Badeni; puspa djuwita (Universitas Bengkulu, 2021)
This study aims to describe the proportion of the cognitive level, affective level, logically and empirically the question items on the School Examination in Social Sciences subjects for the sixth grade students of SDN Kota Bengkulu for the 2019/2020 academic year. This type of research is descriptive research. The subjects in this study were students of class VI SDN 53, SDN 18, and SDN 29 Bengkulu City. The object of this research is the suitability of the questions and answer keys, answers to the school exam. The research instrument used is in the form of a document in the form of a cognitive level report analysis sheet, and an affective level report analysis sheet, questions and answer keys, answers to school exams. The data analysis uses the population level cognitive affective level on the items analyzed, the percentage is calculated, as well as descriptive analysis of material aspects, construction, and language by asking for validation from analysis experts/ experts using Aiken V. The results show that: 1) The proportion of cognitive levels, including levels understand (C2) as many as 14 items (35%), the level of implementing (C3) is 9 items (22.50%), the level of analysis (C4) is 15 items (37.50%), and the level of understanding (C5) as many as 2 items (5%); 2) The proportion of the affective level, including the response level (A2) as many as 1 item (2.5%), the respect level (A3) as many as 3 items (7.5%) and the organizing level (A4) as many as 3 questions (7, 5%); 3) the quality of the items logically based on the results of the validation of material aspects, construction, and language. 40 multiple choice test items show the information displayed in the range> 0.8 with the category